2011
DOI: 10.1111/j.1365-294x.2011.05305.x
|View full text |Cite
|
Sign up to set email alerts
|

A conserved haplotype controls parallel adaptation in geographically distant salmonid populations

Abstract: Salmonid fishes exhibit extensive local adaptations owing to abundant environmental variation and precise natal homing. This extensive local adaptation makes conservation and restoration of salmonids a challenge. For example, defining unambiguous units of conservation is difficult, and restoration attempts often fail owing to inadequate adaptive matching of translocated populations. A better understanding of the genetic architecture of local adaptation in salmonids could provide valuable information to assist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
330
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(341 citation statements)
references
References 66 publications
(83 reference statements)
10
330
1
Order By: Relevance
“…Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70]. Thus, this study supports previous suggestions that the LD block on chromosome Omy5 represents a 'master control region' influencing residency and anadromy in O. mykiss [46,72] and is a parallel selected region [21] that has experienced repeated selection in multiple populations.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70]. Thus, this study supports previous suggestions that the LD block on chromosome Omy5 represents a 'master control region' influencing residency and anadromy in O. mykiss [46,72] and is a parallel selected region [21] that has experienced repeated selection in multiple populations.…”
Section: Discussionsupporting
confidence: 79%
“…Our results provide data from natural populations in California and Oregon that support prior studies on diverse O. mykiss lineages using candidate genes, genome wide association and QTL mapping to explore the genetic architecture of traits associated with life history in O. mykiss, including migration [17,32,42,46,48,[65][66][67][68][69][70][71][72][73][74][75][76]. Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…For example, clinal variations in color in the European barn owl ( Tyto alba ) and tawny owl ( Strix aluco ) seem to be maintained by environmental selection (Antoniazza, Burri, Fumagalli, Goudet, & Roulin, 2010; Karell, Ahola, Karstinen, Valkama, & Brommer, 2011), and clinal variation in allele frequencies in functional genes has been associated with various environmental factors, such as altitude (Bonin, Taberlet, Miaud, & Pompanon, 2006; McCracken et al., 2009), latitude (de Jong, Collins, Beldade, Brakefield, & Zwaan, 2013), and photoperiod (Bradshaw & Holzapfel, 2008). In recent years, several studies have highlighted the utility of genome‐wide scans to investigate mechanisms of population divergence and local adaptation (e.g., resolution of species boundaries in Lake Victoria cichlids, Wagner et al., 2013; parallel adaptation in salmonid fishes, Miller et al., 2012; burrowing behavior in oldfield mice Peromyscus polionotus , Weber, Peterson, & Hoekstra, 2013). An exponential increase in the number of genotyped loci and coverage of the genome over previous methods has also increased power to detect loci that deviate from a neutral model of evolution (i.e., outlier loci) and potentially underlie adaptation.…”
Section: Introductionmentioning
confidence: 99%